INTRAVITREAL CORTICOSTEROIDS IN DIABETIC MACULAR EDEMA: Pharmacokinetic Considerations - Yang, Yit (Retina, 2015)
To review the relationship between kinetics, efficacy, and safety of several corticosteroid formulations for the treatment of diabetic macular edema. METHODS: Reports of corticosteroid use for the treatment of diabetic macular edema were identified by a literature search, which focused on the pharmacokinetics, efficacy, and safety of these agents in preclinical animal models and clinical trials. RESULTS: Available corticosteroids for diabetic macular edema treatment include intravitreal triamcinolone acetonide, dexamethasone, and fluocinolone acetonide. Because of differences in solubility and bioavailability, various delivery mechanisms are used. Bioerodible delivery systems achieve higher maximum concentrations than nonbioerodible formulations. There is a relationship between visual gains and drug persistence in the intravitreal compartment. Safety effects were more complex; level of intravitreal triamcinolone acetonide exposure is related to development of elevated intraocular pressure and cataract; this does not seem to be the case for dexamethasone, where two different doses showed similar mean intraocular pressure and incidence of cataract surgery. With fluocinolone acetonide, rates of intraocular pressure elevations requiring surgery seem to be dose related; rates of cataract extraction were similar regardless of dose. CONCLUSION: Available corticosteroids for diabetic macular edema exhibit different pharmacokinetic profiles that impact efficacy and adverse events and should be taken into account when developing individualized treatment plans.